Molecular structures and fluorescence property of Zn(II), Cd(II) complexes of 3-pyridyl-5-aryl-(1H)-1, 2, 4-triazoles. (16th August 2017) - Mandal, Arkalekha; Patel, Bhisma K.
Graphical abstract: The crystal structures of fluorescence active Zn(II) and Cd(II)complexes of two 3-pyridyl-5-aryl-(1 H )-1, 2, 4-triazole ligands are determined. These complexes exhibit blue violet emission and non-classical C–H⋯S, C–H⋯X (X = F, Cl) hydrogen bonds and π⋯π interactions stabilize their supramolecular assembly. Abstract: The reaction of two 3-pyridyl-5-aryl substituted 1, 2, 4-triazole ligands (trz-1 andtrz-2 ) with M(NO3 )2 and MCl2 (M = Zn II /Cd II ) afforded the metal complexes [Zn(trz-1 )Cl2 ], [Cd(trz-1 )2 (NO3 )2 ] and [M II (trz-2 )2 ](NO3 )2 ·H2 O (M = Zn, Cd). The reaction of Cd(NO3 )2, trz-2 and NaNCS in a 1:1:1 M ratio resulted in the formation of the complex [Cd(trz-2 )2 (NCS)2 ]. These complexes have been characterized by spectroscopic analyses and X-ray crystallography. The crystal structures of the complexes show the presence of classical as well as non-classical C–H⋯O, C–H⋯F and C–H⋯S hydrogen bonds, along with a strong π⋯π interaction between the triazole moieties. The complexes exhibit strong fluorescence emissions both in the solid state and in DMSO solution. Further, the intraligand charge transfer origin of the emission in these complexes has been confirmed by DFT and TD-DFT studies.